Galls of Palaeomystella oligophaga (Lepidoptera, Agonoxenidae) associated with Macairea radula (Melastomataceae) in Neotropical veredas: effects of environment type resource concentration, and plant architecture - Maria Isabela Campos Ruas; Pedro Ivo Alves Barbosa; Sabrina Celie Oliveira e Silva; Mariane Scarcela Durães; Julio Miguel Grandez-Rios; Walter Santos de Araújo (Papéis Avulsos de Zoologia)
Abstract The diversity of galling insects may be associated with abiotic factors, such as hygrothermal stress, and biotic factors of the host plants, such as structural complexity and resource concentration. In the present study, we aimed evaluate the occurrence of galling insects Palaeomystella oligophaga (Lepidoptera, Agonoxenidae) associated with Macairea radula (Melastomataceae) in veredas of northern of Minas Gerais, testing the effect of environmental stress, resource concentration and plant architecture.The study was carried out in three veredas with distinct levels of soil drying and conservation (preserved, intermediate and degraded). In each vereda, were selected 20 individuals of the Macairea radula for galling sampling. For each focal plants were sampled the abundance of galls, plant height (m), number of branches and number of individuals close to the focal plant within a radius of 5 m. In total, were sampled 2,030 galls of Palaeomystella oligophaga on Macairea radula. The abundance of galls differed significantly between the plants of the different veredas, being higher in the plants of the Vereda da Almescla (intermediate conservation level). In addition, the abundance of galls was positively correlated with plant height, and the number of nearby individuals (considering all plant species). Our results demonstrate that both anthropic alterations that lead to the dryness of the veredas, and structural characteristics of the host plants, can affect the occurrence of galls of Palaeomystella oligophaga.